Caribbean human development report 2012 - (UNDP New YorkUS, 2012)
Presents report following from one of the initiatives undertaken by the the UNDP in association with governments, civil society and international agencies; aimed at improving citizen security in Latin America and the Caribbean. Also reflects findings from the analysis of new survey data and consultations involving over 450 experts, practitioners and stakeholders in seven Dutch and English-speaking Caribbean countries.